ANTIPARASITIC EFFICACY OF FIPRONIL IN WISTAR RATS NATURALLY INFESTED BY Polyplax spinulosa (BURMEISTER, 1839) - MORAES, A. C.; PRADO, E. J. R.; BELO, M. A. A. (Ars Veterinaria, 2018)
Based on the importance of pediculosis by Polyplax spinulosa for rodents, this study evaluated two treatments against this louse in naturally infested Wistar rats. 21 adult male rats were randomly distributed into three groups (n = 7): T1 = treated with the association of cypermethrin (5%), dichlorvos (45%) and piperidine butoxide (25%) administered topically by spraying; T2 = treated with fipronil 1 mg. Kg-1 administered topically by spot on; T3 = untreated animals (control). In the initial phase, animals were housed in cages and wrapped in white cotton fabrics for evaluating 4, 12, 24 and 48 hours post-treatment (HPT) to count the number of lice present in the external environment. In the second phase, the groups were transferred to polypropylene boxes for antiparasitic evaluation 7, 14 and 21 days post-treatment (DPT) by direct inspection of eggs and lice presence in the animals. The results showed higher lice counts 4 HPT, representing 41% of the total, and these findings were strongly influenced by the control animals with 20.51%. However, rats treated with fipronil had the highest counts with 24 HPT, representing 14.36% of lice. No variation in lice counts was observed in T1 (pharmacological association). The efficacy study in the animals revealed absence of lice and presence of eggs in treated animals (T1 and T2) at 7 and 14 DPT. In the 21st day, rats treated with the pharmacological association presented lice whereas fipronil treated rats remained only with eggs not hatched. However, this study demonstrated that Fipronil at 1 mg.kg-1 via spot on is an effective option for the control of P. spinulosa in Wistar rats, while treatment with the association of cypermethrin (5%), dichlorvos (45%) and piperidine butoxide (25%) was not effective against eggs viability and hatching, resulting in the return of parasitic infestation.